2021
DOI: 10.1177/1077801220985943
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Within the Context of Patriarchy for Domestic Violence in Urban Uganda

Abstract: This study in urban Kampala contributes to a growing evidence base about the complex contexts within which women make decisions about reporting domestic violence. Based on an intersecting theoretical lens of structural violence, power, and the body, findings suggested that women reported to formal structures primarily for severe physical or economic abuse. Women did not report less severe abuse, and often abandoned reporting even severe abuse, because of the overarching structural patriarchy and violence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…This paper demonstrates the multiple factors that justify violence against women, including the socio-demographic and attitudinal factors that support physical violence against women [ 20 , 24 , 41 ]. The study describes several socio demographic factors that are associated with justification of violence against women including marital status, employment status and educational attainment [ 23 , 44 , 45 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This paper demonstrates the multiple factors that justify violence against women, including the socio-demographic and attitudinal factors that support physical violence against women [ 20 , 24 , 41 ]. The study describes several socio demographic factors that are associated with justification of violence against women including marital status, employment status and educational attainment [ 23 , 44 , 45 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the findings of Uthman and colleagues who found that respondents who were currently married from Malawi, Namibia, Rwanda, and Zimbabwe were less likely to justify IPV than those never married [ 47 ]. This is an indication of contestation of hegemonic masculinity [ 33 ] and hegemonic femininity [ 24 , 41 , 73 ]. These findings may be a reflection of norms shifting–which corroborates with findings from the 2016 Uganda Demographic and Health Survey, that show a decrease in acceptance of violence from 77% to 49% of women and from 64% to 41% of men between 2000/2001 and 2016 [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations